Validación de la versión peruana del cuestionario sobre la salud del paciente (PHQ-9) para tamizaje de depresión en pacientes adultos con cáncer de un hospital público especializado de Lima Metropolitana - De la Flor Valdivia, Martín Alonso (2020)
Approximately 30% of peruvian cancer patients experience clinically significant depressive symptoms, so it is recommended to screen patients for depression in all phases of the disease and treatment. Therefore, the evidence of validity of the scores of the peruvian version of the Patient Health Questionnaire (PHQ-9) for depression screening was evaluated in a population of 500 adult cancer patients from a specialized hospital in metropolitan Lima. Evidence of validity was found based on the content of the questionnaire (V> 0.8). A simple two-factor internal structure that explains 47% of the variance was identified. It presented an adequate goodness of fit (CFI=.942; TLI=.92; AGFI=.946; SRMR=.044; RMSEA=.058). The PHQ-9 and its Affective/Cognitive dimension showed adequate reliability (ω1=.76; ω2=.72), but moderate in the Somatic dimension (ω=.69). The instrument presents scalar measurement invariance when factoring participant’s Sex and Level of Education, configural invariance with Place of application, and differentially measured depression when factoring Civil status and Age groups (ΔCFI>.01). Positive correlations were found between the PHQ-9 and the HADS and its dimensions (r>.6), and with the self-report of depression (r=.71). The most suitable cut-off point for the PHQ-9 was ≥8 (Se=.87; Sp=.77), and it can be used with an application algorithm (Se=.70; Sp=.86), or the abbreviated version PHQ-2 ≥3 (Se=.70; Sp=.85). In conclusion, the evidence of validity of the PHQ-9 justifies its use for the proposed objective.